Optimized electrode arrangement in solar air heater - N. Kasayapanand (2018)
Laminar forced convection inside the solar air heater with various wire electrode arrangements are numerically examined for heat transfer enhancement using electrohydrodynamic technique. The electric field is generated by the wire electrodes charged with DC high voltage ranging from 7.5 to 17.5 kV. Reynolds number corresponding to the flow considered is between 100 and 2000. The numerical modeling of computational fluid dynamics includes the interactions among electric field, flow field, and temperature field. It is found that the enhancement of heat transfer coefficient with the presence of electric field increases in relation with the supplied voltage but decreases when the Reynolds number and the distance between electrode and channel surface are augmented. The optimized electrode arrangement, which obtains the best heat transfer enhancement is investigated incorporating with the pressure drop consideration. The heat transfer enhancement is also depended on the number of electrodes per length and the channel dimension. © 2005 Elsevier Ltd. All rights reserved.